Improvement of Strategic Management of a Tourism Enterprise in the International Market - REGENT, Tatyana Mikhailovna; GLINKINA, Olga Vladimirovna; GANINA, Svetlana Aleksandrovna; MARKOVA, Olga Vladimirovna; KOZHINA, Veronika Olegovna (Journal of Environmental Management and Tourism, 2019)
The article is concerned with the development of approaches to improving a tourism enterprise’s strategy management in the international market. It was established that the strategic choice in the foreign market should be carried out in line with definite goals and results of environment analysis. It was proved that while setting a tourism enterprise’s international market strategy the enterprise should shift its focus to marketing and, at the same time, to focus on the analysis of rivals. It was determined that instability and risks prevent executives from developing corporate development strategies for the international market simultaneously with the transformation of its corporate structure. A portfolio of strategic options, which a tourism enterprise has chosen, should include not only the elaboration of strategies but also ways of their execution, required resources and risk assessment. It was proved that the implementation of strategic management requires permanent control over this process.